2020
DOI: 10.1177/1533033820980117
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA KCNQ1OT1 Promotes Progression of Hepatocellular Carcinoma by miR-148a-3p/IGF1R Axis

Abstract: Accumulating evidence have suggested that long non-coding RNAs (lncRNAs) act as a critical regulator in tumorgenesis. LncRNA KCNQ1OT1 (KCNQ1OT1) has been recently shown to be dysregulated in many cancers. This study was aimed to explore the biological role of KCNQ1OT1 in hepatocellular carcinoma (HCC). In our study, we first observed the expression level of KCNQ1OT1 was distinctly up-regulated in HCC tissues and cell lines compared with adjacent non-cancer tissues and normal liver cell line. And clinical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, deletion of its promoter or early transcript termination results in a loss of KCNQ1OT1 and a disruption of imprinting in the CDKN1C/KCNQ1OT1 domain, which can lead to growth-related disorders (ex. Beckwith-Wiedemann syndrome) and cancer, as well as bi-allelic expression of the entire KCNQ1 domain [ 31 ].…”
Section: Basic Characteristics Of Human Chromosome 11p155 and Lncrna Kcnq1ot1 Genementioning
confidence: 99%
See 1 more Smart Citation
“…However, deletion of its promoter or early transcript termination results in a loss of KCNQ1OT1 and a disruption of imprinting in the CDKN1C/KCNQ1OT1 domain, which can lead to growth-related disorders (ex. Beckwith-Wiedemann syndrome) and cancer, as well as bi-allelic expression of the entire KCNQ1 domain [ 31 ].…”
Section: Basic Characteristics Of Human Chromosome 11p155 and Lncrna Kcnq1ot1 Genementioning
confidence: 99%
“…In addition, Wang et al found that KCNQ1OT1 promoted GC progression by sponging miR-4319 to upregulate the expression of DNA-damage-regulated autophagy modulator 2 (DRAM2) [ 46 ]. Moreover, KCNQ1OT1 is discussed as a ceRNA for miR-148a-3p and a positive regulator for IGF1R in HCC [ 31 ].…”
Section: Regulatory Mechanisms Of Kcnq1ot1mentioning
confidence: 99%
“…An increasing number of studies have confirmed that lncRNAs can act as miRNA sponges and thus reduce their regulatory effects on the target mRNAs; for instance, KCNQ1OT1 acts as miR-216b-5p sponge to attenuate its binding ability to ZNF146 and induce upregulation of ZNF146 expression in colorectal cancer cells [ 25 ]. In addition, KCNQ1OT1 can competitively target miR-148a-3p and consequently promote the expression of the miR-148a-3p target IGF1R gene in hepatocellular carcinoma cells [ 26 ]. KCNQ1OT1 acts as a ceRNA of miR-200a to upregulate the miR-200a downstream forkhead box O3 (FOXO3) expression, thus influencing the pathology of cerebral ischemic stroke [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…KCNQ1OT1 promoted atherosclerosis development by modulating miR-452-3p/HDAC3/ABCA1 pathway (Yu et al 2020 ). Additionally, KCNQ1OT1 exerted tumor-promoting roles in colorectal carcinogenesis (Chen et al 2020b ), non-small-cell lung carcinoma (Dong et al 2019 ), hepatocellular carcinoma (Xu et al 2020 ), bladder cancer (Wang et al 2019a ), glioma (Ding et al 2020 ), osteosarcoma (Wang et al 2019b ), gastric cancer (Wang et al 2020 ) and OC (Liu et al 2020 ). Consistent to research of Liu et al ( 2020 ), we found that KCNQ1OT1 expression was increased in OC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%